2011
DOI: 10.1002/pola.24909
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water addition on the cure kinetics of an epoxy‐amine thermoset

Abstract: In this study, the effect of water addition on cure kinetics in an epoxy-amine thermoset was investigated. Near FTIR spectra demonstrated that a small amount of water addition significantly accelerated the cure reaction in terms of epoxide conversion, with water acting as a catalyst for the reaction. Use of a modified mechanistic model allowed direct comparison of the effect of hydroxyl groups generated from water addition to those generated from the polymer chain. The comparison of those kinetic parameters sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 50 publications
2
20
1
Order By: Relevance
“…It is known that the presence of minor amounts of water is interfering with the epoxy/ amine curing step: water will affect the epoxy cure rate and also decrease the final crosslink density and glass transition temperature, leading to worse mechanical properties of the epoxy thermoset. [69][70][71] These effects are important for the development of the coupling agent/epoxy interface (interphase) and might lead, as a consequence, to an inferior epoxy/SS adhesion.…”
mentioning
confidence: 99%
“…It is known that the presence of minor amounts of water is interfering with the epoxy/ amine curing step: water will affect the epoxy cure rate and also decrease the final crosslink density and glass transition temperature, leading to worse mechanical properties of the epoxy thermoset. [69][70][71] These effects are important for the development of the coupling agent/epoxy interface (interphase) and might lead, as a consequence, to an inferior epoxy/SS adhesion.…”
mentioning
confidence: 99%
“…An incomplete condensation during the air drying treatment leads to an inferior or disordered siloxane network, which can further condense during the subsequent thermal curing of the epoxy formulation, thereby releasing water. This water might interfere with the epoxy curing reaction, lowering its crosslink density, glass transition temperature and mechanical properties, which leads to an inferior SS/epoxy interfacial strength [43][44][45]. Fig.…”
Section: Optimisation Of the Silane Condensation Conditions With Respmentioning
confidence: 98%
“…Noticeably, the intensity ratio of I 3775 cm21 /I 1813 cm21 decreased from 110% (EP) to 51% [EP/FAP-HNT (15)], in which I 1813 cm21 is the intensity of the CAH vibrations of EP. Choi et al 24 reported the effect of water addition on the curing kinetics of an EP-amine thermoset. The FTIR spectra demonstrated that a small amount of water addition significantly accelerated the curing reaction in terms of epoxide conversion, with water acting as a catalyst for the reaction.…”
Section: Preparation and Characterization Of The Fap-hnt And Ep/fap-hmentioning
confidence: 99%